Intergenerational care: an exploration of consumer preferences and willingness to pay for care. (3rd August 2018) - Vecchio, N.; Radford, K.; Fitzgerald, J. A.; Comans, T.; Harris, P.; Harris, N.
ABSTRACT: Objectives: To identify feasible models of intergenerational care programmes, that is, care of children and older people in a shared setting, to determine consumer preferences and willingness to pay. Method: Feasible models were constructed in extensive consultations with a panel of experts using a Delphi technique ( n = 23) and were considered based on their practical implementation within an Australian setting. This informed a survey tool that captured the preferences and willingness to pay for these models by potential consumers, when compared to the status quo. Information collected from the surveys ( n = 816) was analysed using regression analysis to identify fundamental drivers of preferences and the prices consumers were willing to pay for intergenerational care programmes. Results: The shared campus and visiting models were identified as feasible intergenerational care models. Key attributes of these models included respite day care; a common educational pedagogy across generations; screening; monitoring; and evaluation of participant outcomes. Although parents were more likely to take up intergenerational care compared to the status quo, adult carers reported a higher willingness to pay for these services. Educational attainment also influenced the likely uptake of intergenerational care. Conclusions: The results of this study show that there is demand for the shared campus and the visiting campus models among the Australian community. The findings support moves towards consumer-centric models of care, in line with national and international best practice. This consumer-centric approach is encapsulated in the intergenerational care model and enables greater choice of care to match different consumer demands.